Influence of the electrical parameters on the ultrasonic probe impedance and the reflected pulses - G. ŁYPACEWICZ (Archives of Acoustics, 2014)
Basing on the modified Mason's equivalent circuit of an ultrasonic transmitting-receiving probe [3], [4] the influence of compensating inductances, a coaxial cable, wire conductors and parallel resistance on the probe immitance and the reflected pulses is discussed. The influence of the wire conductors connecting a transducer with a coil or a coaxial connector for large diameters (i.e. 20 mm) and high frequencies (i.e. 10 MHz) on the probe immitance should be taken into account. The influence of the coaxial cable on the probe immitance and the reflected pulses depends on the electrical impedance of a probe. The compensating circuit containing three inductances - two in series and one parallel is discussed. The influence of the parallel resistance on the reflected pulse is shown and compared with the influence of transducer backing. It was shown that the length of transmitting burst should be chosen depending on the frequency band-width of the probe.